Interpretive approaches to global climate governance : (de)constructing the greenhouse - Methmann, Chris; Rothe, Delf; Stephan, Benjamin (Interventions, 2013)
This work seeks to fuse a global governance perspective together with different interpretive approaches, offering a novel way of looking at international climate politics. Equipped with a common interpretive tool-kit, the authors examine different issue-areas and excavate the contours of an overall pattern